The Emergency Medical Services of Local Administrative Sectors in the Southern Borders, and Related Factors - บินสะแหละหมัน, นุสรีนา; ประณีต, ประณีต; ศรศรีวิชัย, วรสิทธิ์ (Princess of Naradhiwas University Journal, 2018)
This descriptive study aimed to describe 1) the situation of the emergency medical services (EMS) organized by Local Administrative Sectors (LAS) in the Southern Borders, 2) factors related to EMS provision. The population was the chief executive of LAS in the Southern Borders who provided or none of EMS. The data were collected using the questionnaire. on the management and operation of EMS of LAS. Content validity index was judged by 3 experts. The reliability of the Questionnaire was verified by using the Kuder-Richardson coefficient, yielding values of 0.94. Data analyzed by descriptive statistics including percentage, mean, standard deviation, median, interquartile range and analysis of factors associated with EMS provision by LAS in the Southern Borders using Binary Logistic Regression. The returned questionnaires was 273 (64.8%) which showed that about 53.5 % of LAS have provided EMS which stated in the written policies of EMS (73.3%) and the adequate budget to support (67.1%). The majority of them had a set of operations with basic emergency medical personnel (namely FR) (94.5%), and had assigned a responsible person for this job (84.9%). The top activities performed which achieved the EMS standards more than 80% were ability to communicate with the dispatch center / hospital for assistance (94.5%), followed by having a received call notification 24 hours (93.8 %) respectively. The provision which performed less than 60 % of the standards was using a GPS navigation system (20.5%). The LAS who has not provided the EMS (46.5 %) due to insufficient budget (81.9%). The important factors that can increase the opportunities of LAS to operate the EMS system in the Southern borders were 1) having the written policy of the EMS 2) budget to support the EMS and 3) a concern of administrator. The findings from the study can be used as a basis for better or effective development of EMS provision by LAS in the area.